The Heat of Competition: Assessing Climate Vulnerabilities and Adaptive Governance in Endurance, Winter, and Youth Sports - Gondo Thembelihle (International Journal of Climate Conditions, 2026)
Background: Climate change is fundamentally reshaping the environmental parameters of global sport, posing unprecedented risks to athlete health, safety, and performance. As rising temperatures, frequent extreme heat events, and deteriorating air quality become the new normal, athletic environments from community fields to elite international arenas face an existential threat. Purpose: This study provides an interdisciplinary synthesis of the multifaceted impacts of climate change on athletes, integrating evidence from sports medicine, environmental health, and climate science. It examines the physiological burden of environmental stressors specifically heat-related illness (HRI), cardiovascular strain, and respiratory distress alongside the psychological stressors triggered by disrupted seasons and unsafe competitive conditions. Methodology: Using a mixed-methods design, the research investigates the specific vulnerabilities of endurance, winter, and youth athletics. Findings: The results highlight a stark Adaptation Gap. While tactical adaptation by coaches is high (80%), a significant Governance Gap persists: although 75% of athletes recognize climate change as a direct threat, only 40% believe governing bodies are responding adequately. Data reveals that 72% of endurance athletes report heat-related symptoms, and 65% of youth athletes who possess immature thermoregulatory systems struggle with heat-load management. Vulnerabilities are disproportionately concentrated in endurance disciplines and resource-constrained settings that lack climate-resilient infrastructure. Conclusion: Through an analysis of case studies from major international competitions, the research identifies an urgent need for a paradigm shift in sports governance. Safeguarding athlete well-being must transition from a peripheral medical concern to a core requirement of sustainable event planning. The study concludes that the future of sport depends on moving beyond reactive measures toward structural, policy-driven resilience. By positioning the athlete at the centre of the climate crisis, this research advocates for the sporting world to transition from a vulnerable sector to a powerful platform for public health resilience and climate advocacy. Future research should examine interdisciplinary studies that integrate climate science, sports medicine, and organizational governance.
Keywords: Athlete health; Climate change; Environmental stressors; Heat-related illness; Physiological strain; Sports governance; Sports medicine; climate adaptation; global health